DETERMINAÇÃO DO CONSUMO DE ÁGUA E DO COEFICIENTE DE CULTURA DA ABÓBORA NA REGIÃO DE BOTUCATU, SP - Klosowski, Elcio Silvério; Lunardi, Dalva Martinelli Cury [UNESP]; Sandanielo, Aquiles (Departamento de Engenharia Agrícola - UFCG, 1999)
Summer squash ( Cucurbita pepo L.) water consumption was determined by water table lysimeters in Botucatu region (latitude 22º51'S, longitude 48º27'W and altitude 786 m). The crop showed higher water consumption during the blossom and fruit development stages. The total water consumption was 231.52 mm, in a crop season development of 70 days. The crop coefficients obtained varied between 0.68 and 1.96.

O consumo de água pela cultura de abóbora italiana ( Cucurbita pepo L.) cultivar Caserta, foi avaliado através de um conjunto de lisímetros de nível de lençol freático na região de Botucatu, SP (latitude 22º51'S, longitude 48º27'W e altitude 786 m). A cultura apresentou maior consumo hídrico no tempo entre a floração e o desenvolvimento dos frutos. O consumo total de água para um ciclo de 70 dias foi de 231,52 mm. Os coeficientes de cultura (kc) obtidos variaram entre 0,68 e 1,96.
WATER CONSUMPTION AND CROP COEFFICIENT DETERMINATION OF SUMMER SQUASH IN BOTUCATU REGION
Keywords: Cucurbita pepo L; crop coefficient; evapotranspiration; Cucurbita pepo L; coeficiente de cultura; evapotranspiração